Seguimiento del desempeño del rol profesional de los egresados de la Facultad de Odontología Universidad Antonio Nariño Sede Ibagué en la zona Sur y el municipio de Cajamarca, 2020. (2021)
This project aims to monitor the graduates of the Ibague-headquarters School of Dentistry between the years 2001-2020-II, taking into account aspects of statistical traceability to show the impact they have had in the labor and social sphere. In turn, it will be a tool that allows graduates to show their integration with their alma mater. The role of the graduate, their contribution and experience acquired in their work and professional life, is considered. This project has the application of an electronic survey, via google drive. Where questions are formulated aimed at knowing each of these aspects to have a better visibility of what has happened in their lives immediately after graduating from university. Keywords: graduate, follow-up, impact role